Televising truth commissions: the interaction between television, perpetrators, and political transition in South Africa - Anderson, Michelle E (Centre for Film and Media Studies, 2020)
This research explores the portrayals of perpetrators in television broadcast coverage of truth commissions within politically transitioning societies, particularly how these discourses may influence the perceptions and experience of transition out of conflict. It focuses on the narratives constructed around apartheid-era perpetrators who participated in the South African Truth and Reconciliation Commission (TRC) as shown by the South African Broadcasting Corporation's (SABC) weekly broadcast, Truth Commission Special Report. It also considers how this informs perpetrators in speaking about their own histories. The SABC broadcasts aired between the 21st of April 1996 and the 29th of March 1998. It acted as a key news source on the workings of the TRC for a large group of citizens. An average of 1.1 to 1.3 million people tuned in each week for the first year, and an average of 510,000 people tuning in during its second year on air.1 The TRC hearings were recorded and filmed, and parts of these recordings were included in the SABC programme, along with further research by Special Report journalists. This included stories from the apartheid era that were not told through the TRC, further interviews with perpetrators, victims, bystanders, and communities, as well as reference to news and legal documents. As SABC describes it, the Truth Commission Special Report series “contributed to the TRC's pursuit of revealing the truth about, and engendering a deeper engagement with, South Africa's past conflicts.”2 The series was hosted and produced by well-known anti-apartheid journalist and Afrikaner Max du Preez, whose own identity became central to the narrative put forth. His team of journalists and producers included other Afrikaners such as his long-time colleague Jacques Pauw, and the young Anneliese Burgess. Otherwise, “his team of journalists varied over the twenty-three months of the series, generally including five and seven people who were racially, ethnically, and linguistically diverse.”3 As South Africa transitioned out of the apartheid state, transparency of the transitional mechanisms taking place was essential for the transformation of governance and the appearance of accountability.4 This demand acted as one of the driving forces for the intense media involvement in the country's chief transitional process, namely the TRC. This research hinges on the hypothesis that the media's involvement in the South African transitional process went beyond the provision of transparency and may have influenced people's perceptions and experience within the transition per assertions by scholars such as Parver and Wolf, Fischer, Kent, and Mihr, 5 among others. It uses this as a starting point to then investigate the series' narrative as a source of these perceptions and the subsequent experiences of the subjects. This points not only to outcomes, but also their influencing factors with the intent to suggest recommendations for more intentional media coverage of political transitions, with perpetrators being one facet of such.